Vprašalni nagovori in druge besedilotvorne strategije v intervjujih na radiu in v podkastu - Verovnik, Tina (Teorija in praksa, 2023)
The article analyses the frequency of interview addresses, as typologically defined by Korošec (1998), in four radio interviews and four interview podcasts featuring the same guests. In addition, some other textual strategies, such as supporting signals and role reversals, are analysed. The journalistic interview is a highly institutionalised form of one-way dialogue, which has indeed been proven in radio interviews to a considerable extent. In podcasts, however, due to the different production and listening practices, speech usually displays more characteristics of everyday discourse, as was displayed in the choices of interview addresses and other textual strategies in the analysed podcasts.
Keywords: everyday speech; Govor; interview; interview address; intervju; intervjujski nagovor; podcast; podkast; Radijski intervjuji; radio; vsakdanji govor